Pengaruh Lingkungan Kerja dan Pengawasan terhadap Kinerja Pegawai pada PT. POS Indonesia Cabang Sibolga - Anwar Anwar; Yenni Sofiana Tambunan; Sriayu Aritha Panggabean (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of work environment and supervision on employee performance at PT Pos Indonesia both partially and simultaneously. This study employed a quantitative approach with an associative research design. The population and sample consisted of 49 employees using a saturated sampling technique. Data were collected through questionnaires and interviews, while data analysis was conducted using multiple linear regression with the assistance of IBM SPSS Statistics. The results showed that the work environment had a positive and significant effect on employee performance with a t-count value of 3.547 greater than the t-table value of 2.013 and a significance value of 0.001 < 0.05. Supervision also had a positive and significant effect on employee performance with a t-count value of 17.750 greater than the t-table value of 2.013 and a significance value of 0.000 < 0.05. Simultaneously, the work environment and supervision had a positive and significant effect on employee performance with an F-count value of 175.638 greater than the F-table value of 3.20 and a significance value of 0.000 < 0.05. The coefficient of determination indicated that 87.9% of employee performance was influenced by work environment and supervision, while the remaining 12.1% was influenced by other factors outside this study. Therefore, the better the work environment and supervision implemented by the company, the higher the employee performance at PT Pos Indonesia.